Mass customization with additive manufacturing: Blessing or curse for society? - Julian Schwierzy; Tobias Wenzel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Additive Manufacturing (AM) enables mass customization and has thereby the potential to revolutionize traditional manufacturing. In this paper, we examine how the adoption of AM affects competition and welfare in traditionally standardized product markets. Analyzing a game-theoretical model of spatial product differentiation, we find a decline in standardized product prices. In contrast, the price of customized products will exceed the price level of the initial market. These price changes are accompanied with a reduction in the number of traditional manufacturers. In terms of welfare, AM adoption increases total surplus. However, it can be detrimental for consumer surplus if the competitive advantage of AM technology is excessively large. Based on these findings, we discuss policy implications for the manufacturing industry. We recommend complementary measures of ensuring the competitive environment for firms with AM technology and subsidizing their fixed cost in order to realize benefits for both consumers and producers.
Keywords: L11; L22; L23; O33; 330; Technology adoption; Market structure; Welfare; Product differentiation; Industrial Additive Manufacturing